BVAS, IReV and Democratic Elections in Nigeria - Ugo Chuks Okolie (Universitas Negeri Makassar, 2024)
The BVAS is a technological tool used to identify and accredit voters' fingerprints and facial recognition prior to voting, whereas the IReV is an online portal where polling unit level results are uploaded, transmitted, and published for the public. The public can set up individual accounts at the online portal's front end, giving them access to all uploaded results stored as PDF files. The public will be more confident in the process and transparency will increase if results are made available down to the polling unit level. Despite the promises of new technologies, dishonest INEC officials used a single button click to steal, rig, and annul voter decisions in elections. In light of this, this study evaluated the performance of BVAS and other new electoral technologies and innovations in the Nigerian general elections of 2023. Qualitative research design and content analysis was used in this study. The study comes to the conclusion that while INEC deployed BVAS and other new electoral technologies and innovations to improve electoral integrity and inspire public confidence in the electoral process, those efforts were not flawless and some INEC officials compromised the electoral process. Undoubtedly, the use of BVAS and other electoral technologies could prevent election rigging and boost public confidence in election results, but some failures in the use of BVAS and IReV have been noted. Therefore, this study recommends among others that the electoral umpire in future general elections should be impartial and nonpartisan. This will ensure that all candidates have an equal chance to win and that Nigerian elections will be held without incident.